EPR relaxation : progress in hardware and analysis methods - Roberts, Peter Joseph (2014)
Dynamic nuclear polarization (DNP) is a technique for enhancing the sensitivity of nuclear magnetic resonance (NMR) experiments by increasing the polarization of the nuclear spins. DNP experiments are often characterized by the enhancement which is achieved, and the enhancement build-up rate. These parameters are strongly influenced by electronic and nuclear relaxation processes. The purpose of the work presented in this thesis was to develop hardware and analysis methods for studying relaxation in electron paramagnetic resonance (EPR) and NMR. Two novel probes for combined NMR and longitudinally detected EPR experiments have been built. The first of these probes is designed for low temperature NMR, EPR and DNP experiments, with the main focus being relaxation studies in typical low-temperature DNP conditions. The second probe is designed for high temperature cryoporometry studies of lignin degradation. Relaxation data in magnetic resonance often exhibits multi-exponential decay. An algorithm for performing a Laplace inversion of multi-exponential relaxation data, and extracting distributions of time constants, is described. The algorithm, which is based on Tikhonov regularization, uses a uniform penalty and a zero-crossing penalty to stabilize the solution, but does not use a non-negativity constraint, so relaxation spectra with both positive and negative peaks can be produced. Two experiments to study relaxation and other dynamic processes in samples containing organic radicals have been performed. The first of these was designed to study saturation, relaxation and spectral diffusion processes in EPR during continuous microwave irradiation. The second experiment measured relaxation of DNP-enhanced nuclear polarization, and revealed an offset dependence of the relaxation behaviour. Both experiments were performed using the low-temperature probe, and the data was analysed using the Laplace inversion algorithm.